MENGHITUNG PERKALIAN DENGAN BENDA-BENDA TERDEKAT : (Calculating Multiplication with the Closest Objects) - Amir, Nur Fadhilah (Uniqbu Journal of Exact Sciences, 2021)
Students still have difficulty calculating multiplication. This study aims to improve the multiplication ability of grade IV SD Negeri 1 Airbuaya students. The research location is SD Negeri 1 Airbuaya with a total of 16 students. The data in this study were obtained from interviews, questionnaires, observation results, and evaluation results. This research was carried out in two cycles which were carried out based on the stages: (1) compiling an activity plan, (2) carrying out actions, (3) observing, and (4) analyzing which was carried out by reflection. The results showed that the results of the researchers 'observations on pre-action in classroom learning, the students seemed less active, easily bored, and the students' attention to the teacher's explanation was very small. In the action cycle 1, mastery of the material before learning was given 31%, after the activity took place 58% active student activity, 30% moderate student, and 12% passive student. 62% active cooperation, 28% medium students, and 10% passive students. Meanwhile, the average evaluation result is 68 with 33 students completing and 16 unfinished students. Result of action in cycle 2, mastery of material before action 48%. After the action was carried out, 78% active student activity, 18% moderate student and 4% passive student activity. 84% active student cooperation, 14% medium students, and 2% passive students. The results of the evaluation on average are 76 with 13 students completing and 3 incomplete students.